Inteligência analítica nas organizações : levantamento bibliométrico e de linhas de pesquisa emergentes - Araujo, William Pascheti (2022)
In a more uncertain and competitive scenario it is a sine qua non condition for firms to develop identification, analyzing and business models’ transformation capabilities to continue satisfying its increasingly clients ‘requests. It is in this volatile scenario, which Analytical Intelligence solutions emerge as adequate solutions for supporting senior management in their decisionmaking process towards outstanding firm and financial performance. Thus, the objective of this research is to map what are the papers, authors and journals that are contributing to the expansion of this field of research in the Information Technology area as well as, presenting emergent research in the Analytical Intelligence´s research field. The raison d´être of this research was identified based on an analysis performed by the authors in which, last bibliometric studies elaborated in Portuguese about Analytical Intelligence, date from 2018. To attend this research´s objective, a bibliometric study was conducted to present the most relevant publications, authors, journals in the Analytical Intelligence field via a cocitation analysis and classification of the main clusters found with this procedure. As a result of this cocitation analysis, three clusters were identified, which are: Analytical Intelligence Foundation, Analytical Intelligence for Supply Chain Management and Analytical Intelligence related to firm performance, capabilities, and resources. From these clusters, future research fields scenario was presented with special attention to studies focused on the practical benefits of Analytical Intelligence´s usage in different sectors, such as: Tourism, Healthy and Retail.